Correlation of Responsive Caregiving with Child Development - Ulfi Rifki Ichromy; Ahmad Suryawan; Mira Irmawati (Journal of Public Health and Pharmacy, 2025)
Introduction: Caregiving or parenting significantly impacts a child's growth and development. Responsive caregiving is regarded as the optimal caregiving model. Current research pertains to responsiveness and the cognitive and psychosocial development of children. However, research linking responsive caregiving to children’s development is still rarely conducted. This study aimed to determine the correlation between responsive caregiving patterns and child development. Methods: This cross-sectional study was conducted on children aged 48 to 72 months in Bina Anaprasa kindergartens Surabaya within May 2024. Data collection was obtained through interviews and observation of interactions between caregivers and children. Responsiveness was measured using responsiveness criteria in the HOME assessment score. Child development was measured using Denver II. Denver II tests child development as general, which consist of gross-motor, language, fine motor and personal-social developments. Data analysis used a correlation test based on each variable’s scale. Ethical approval was obtained from Komite Etik RS Dr. Soetomo, and participants provided written informed consent. Results: A total of 67 children from 4 kindergartens were included in this study. This study found 7 children (10.5%) with developmental delay. A significant relationship was found between parenting responsiveness and general child development [p=0.021; OR: 7.5 (1.31-42.76)]. If specified, fine motor development have significant relationship (p=0.006). However, there was no significant correlation between responsive caregiving and gross motor development (p=0.299), language development (p=0.060), and personal-social development (p=0.076). Conclusion: Responsive caregiving was correlated with general child development and fine motor development. However, there was no correlation between responsive caregiving and other development parts. Although responsive caregiving is already widely recommended for optimal child growth and development, it is not routinely evaluated. We recommend routine assessment and caregiving training as early intervention. The limitation of this study is that the sample were homogeneous, and did not involve other influential variables such as nutritional intake and socioeconomic status. Further study addressing this limitation can be conducted.